2022
DOI: 10.3389/fsurg.2022.791945
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Modified Nasobiliary Fixation and Drainage Technique

Abstract: ObjectivesWe investigated the clinical efficacy of a modified nasobiliary fixation and drainage technique which was designed in an attempt to reduce unplanned extubation and tube blockage and improve bile drainage and the comfort of catheterized patients.MethodsFrom January 2019 to December 2020, 230 patients receiving Endoscopic nasobiliary drainage (ENBD) during hospitalization were recruited to this study. Participants were randomly allocated to 2 groups by using the block randomization method: in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The study found that leaving the nasobiliary tube in place did not provide additional clinical bene ts to patients but instead prolonged operation time and increased patient discomfort [18]. Another study showed that using an improved "tube-nose-ear" three-step xation technique signi cantly reduce nausea and vomiting after ENBD, facilitate biliary drainage, and improve patient comfort [19]. For postoperative nausea and vomiting due to anesthetic drugs, Kovac emphasized the importance of multimodal pain management (including preoperative regional anesthesia and reducing the use of opioid drugs) and prophylaxis with combination drug therapy (such as dexamethasone and 5-HT3 receptor antagonists).…”
Section: Post-ercp Nausea and Vomitingmentioning
confidence: 99%
“…The study found that leaving the nasobiliary tube in place did not provide additional clinical bene ts to patients but instead prolonged operation time and increased patient discomfort [18]. Another study showed that using an improved "tube-nose-ear" three-step xation technique signi cantly reduce nausea and vomiting after ENBD, facilitate biliary drainage, and improve patient comfort [19]. For postoperative nausea and vomiting due to anesthetic drugs, Kovac emphasized the importance of multimodal pain management (including preoperative regional anesthesia and reducing the use of opioid drugs) and prophylaxis with combination drug therapy (such as dexamethasone and 5-HT3 receptor antagonists).…”
Section: Post-ercp Nausea and Vomitingmentioning
confidence: 99%
“…ENBD is a simple and easy approach for relieving biliary obstruction by reducing biliary pressure, thereby rapidly relieving the symptoms of biliary obstruction and controlling biliary infection[ 109 , 110 ]. However, it is important to note that the nasobiliary duct can irritate the throat, is prone to slippage or blockage, and has the disadvantage of removing abundant bile salts, which can further cause disorders of the water-electrolyte balance and digestive dysfunction in patients[ 111 ].…”
Section: The Treatment Of Oj: Medication and Surgerymentioning
confidence: 99%